The Three-way Interaction Effects of Gender, Supervisor’s Gender, and Country on the Conflict-management Strategies of Millennials: A 10 Country Study - Rahim, A.; Katz, J.; Ma, Z.; Yilmaz, H.; Lassleben, H.; Rahman, S.; Silva, M. G.; Bibi, Z.; Shaw, L.; Fernandez, T.; Yee, L. M. (IAAM virtual conference, 2021)
This field study investigates the interactive effects of Millennial employee’s gender, supervisor’s gender, and country culture on the conflict-management strategies in ten countries (USA, China, Turkey, Germany, Bangladesh, Portugal, Pakistan, Italy, Thailand, and Hong Kong). This exploratory study extends past research by examining the interactive effects of gender on conflict-management strategies within the worker–supervisor relationship in a single generation of workers, Millennials. The Rahim Organizational Conflict Inventory-II (ROCI-II) was used to assess the use of the five conflict-management strategies (integrating, obliging, dominating, avoiding, and compromising.). Data analysis found conflict-management strategies employed in the workplace are influenced by the interaction of worker and supervisor genders and the national context of their work. Data analysis (N = 2,801) was performed using the Multivariate Analysis of Covariance (MANCOVA). Implications for leading global teams and training programs for mid-level Millennials are offered. The limitations of our study along with future research opportunities are also provided.